Cytosine arabinoside-metabolizing enzyme genes are underexpressed in children with MLL gene-rearranged acute lymphoblastic leukemia - J.F. Mata; C.A. Scrideli; R.P. Queiroz; B.O. Mori; M. Emerenciano; M.S. Pombo-de-Oliveira; L.G. Tone (Brazilian Journal of Medical and Biological Research, 2006)
Infant acute lymphoblastic leukemia (IALL) is characterized by mixed lineage leukemia (MLL) gene rearrangements, unique gene expression profiles, poor prognosis, and drug resistance. One exception is cytosine arabinoside (Ara-C) to which IALL cells seem to be more sensitive. We quantified mRNA expression of Ara-C key enzymes in leukemic lymphoblasts from 64 Brazilian ALL children, 15 of them presenting MLL gene rearrangement, and correlated it with clinical and biological features. The diagnosis was based on morphological criteria and immunophenotyping using monoclonal antibodies. MLL gene rearrangements were detected by conventional cytogenetic analysis, RT-PCR and/or fluorescence in situ hybridization. The DCK and HENT1 expression levels were determined by real-time quantitative PCR using SYBR Green I. Relative quantification was made by the standard curve method. The results were analyzed by Mann-Whitney and Fisher exact tests. A P value of £0.05 was considered to be statistically significant. DCK and HENT1 expression levels were significantly lower in children with MLL gene-rearranged ALL compared to children with MLL germ line ALL (P = 0.0003 and 0.03, respectively). Our results differ from previous ones concerning HENT1 mRNA expression that observed a higher expression level in MLL gene-rearranged leukemias. In conclusion, the expression of the genes related to Ara-C metabolism was lower in MLL-positive children in the sample studied, suggesting the presence of population differences in the expression profile of these genes especially for HENT1.